Preschool children learning a foreign vowel through a two-day listen-and-repeat training - Repo, Liina (My University, 2019)
This thesis concentrates on second language learning during childhood. The theoretical part of the thesis examines different kinds of second language learning theories from the perspective of foreign language learning in children. The empirical part of the study utilises the theories and models presented in the theoretical part in determining the theoretical framework for the study to shed light on the questions around second language learning during childhood in the best possible way. The aim of this thesis is to study how listen-and-repeat production training affects children’s ability to perceive and produce a non-native vowel, which is theoretically as challenging as possible. The non-native vowel was embedded in a pseudo-word context. The stimuli used in the study were two semisynthetic pseudo-words, /tʉ:ti/ and /ty:ti/. Primary interest was pointed to the pseudoword /tʉ:ti/, as it contained the target vowel /ʉ/ which is phonemically irrelevant in Finnish, but relevant in Swedish. The participant group consisted of 12 Finnish preschool girls, aged 6–7. The participants participated in the study on two consecutive days which consisted of two training and two recording sessions. The recorded productions were analysed acoustically to find out the first two formant frequencies of the target vowel /ʉ/ and the non-target vowel /y/. The values were then statistically analysed. The results revealed that the participants learned to produce the non-native vowel in two days, after four training sessions. The results support earlier research on foreign language speech sound learning by children. Children are fast learners and benefit from listen-and-repeat training in learning foreign language speech sounds.
Keywords: L2 learning, children, speech production, speech perception